Host genomic convergence, rather than gut microbiome convergence, underlies the convergent evolution of subterranean adaptation in mammals - Li, Kexin; Liu, Yixin; Zhang, Yehao; Fan, Zhenxin; Hu, Xiangxu; Lai, Xinlei; Wei, Fuwen; Hu, Yibo (Cell reports (Cambridge), 2025)
Subterranean mammals exhibit diverse traits for underground life, making them ideal models for studying molecular mechanisms of adaptation and convergence in extreme environments. To investigate these processes at both the genomic and gut microbiome levels, we assemble a chromosome-level genome of the Chinese bamboo rat (Rhizomys sinensis) and identify an expansion of the Hsp90 gene family, potentially associated with hypoxia adaptation. Transcriptomic analysis reveals gene expression changes related to tooth development and visual perception in the Chinese bamboo rat. Furthermore, we identify convergent genetic changes related to vision, hearing, immunity, and hypoxia among subterranean mammals, with widespread Krt9 pseudogenization potentially linked to long-term burrowing behavior. However, the gut microbiome shows no structural or functional convergence in subterranean mammals, being shaped by host phylogeny and gut morphology rather than habitat. These findings suggest that host genomic rather than gut microbiome convergence underlies convergent subterranean adaptation, offering multi-omics insights into subterranean adaptation. [Display omitted] •Chromosome-level genome assembly of the Chinese bamboo rat•Comparative genomics reveals Hsp90 gene family expansion associated with hypoxia adaptation•Multi-omics analyses identify convergent genomic changes across subterranean mammals•Gut microbiome structure and function show no convergence in subterranean mammals Li et al. perform multi-omics comparative analyses in subterranean mammals and identify convergent genomic signatures associated with adaptation to underground life, while their gut microbiomes show no structural or functional convergence. These findings suggest that host genome convergence, rather than microbiome convergence, underlies adaptation to subterranean environments across subterranean mammals.